Comparison Between Intraventricular and Intraparenchymal Intracranial Pressure Monitoring in Asian Patients With Severe Traumatic Brain Injury. Issue 2 (May 2016) - Li, Zhiqiang; Quan, Zhe; Zhang, Ning; Zhao, Jun; Shen, Dongqing
Abstract : Objective: Traumatic brain injury (TBI) is a significant cause of mortality and morbidity. Intraventricular and intraparenchymal intracranial pressure (ICP) monitors are most widely used in clinical practice. There has been little investigation into the comparison between these 2 ICP monitoring sites. Methods: Patients with severe TBI were admitted in this prospective study. Data on demographics and injury characteristics were registered. Glasgow Outcome Scale Extended 6 months after injury, intensive care unit (ICU) length of stay, and monitoring-related complications were registered. Results: Intraparenchymal ICP monitoring group had a shorter duration of ICP monitoring (4.1±3.6 vs. 7.6±5.8 d, P <0.01). The ICU length of stay was similar in the 2 groups (15.6±11.8 vs. 17.9±13.2 d, P =0.15). Device-related complications were lower in the intraparenchymal group (10.7% vs. 32.8%, P <0.01), although more patients received surgical decompression (32% in intraventricular vs. 40.1 in intraparenchymal group, P =0.04). On multivariate logistic analysis, age, initial Glasgow Coma Scale score, and size of midline shift were independent predictors for mortality and unfavorable survival. Conclusions: Intraparenchymal pressure monitoring in patients with severe TBI is associated with shorter ICP monitoring, hospital length of stay, and less device-related complications compared with the intraventricular method.